Childfree Dikalangan Masyarakat Millenial Studi Lintas Agama (Islam, Kristen dan Hindu) - Ahmad Soleh Hasibuan; Aminah Lubis (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
The term Childfree has recently become a sensation among millennials today, not long after public figure Gita Safitri Devi and her husband Paul Andre Partohap stated on their social media account that they intended not to have children. Childfree is actually not a new issue, but the term childfree has been around since the end of the 20th century and has spread throughout the world along with the development of liberalism throughout the world. Childfree is a choice in a household relationship, namely a decision for a husband and wife not to have children on purpose. This phenomenon is an interesting issue to discuss from various perspectives, one of which is from a religious perspective. Of course, each religion will have different views in responding to the issue of childfree in accordance with the teachings of their respective religions. The method used in this research is a qualitative research method, library research approach. Research originating from books, journals, videos, and research that has been conducted, is then analyzed in depth. This research concludes that seen from a religious perspective, in this case there are three religions that are the focus of reference for researchers, namely Islam, Christianity and Hinduism, that chidfree is something that is contrary to the principles in their teachings. In responding to the Chidfree problem, there is a solution provided by each religion as long as it is considered humane and does not eliminate the benefits, or brings harm and does not conflict with religious rules and principles.